Digital divides among microenterprises: Evidence from sub‐Saharan Africa - (:unkn) unknown (My University, 2023)
AbstractThis paper investigates digital inequalities in usage within African informal sectors. In particular, we examine whether the uneven digital diffusion is embedded in pre‐existing socio‐economic inequalities. After identifying three segments of informal firms, we rely on multivariate and decomposition analyses to identify predictors of usage of digital technologies for business purposes and explain usage gaps between segments. Our findings suggest that digital inequalities are rooted in the vertical heterogeneity of informal sectors, with some firm characteristics significantly predicting professional use of digital technologies. In addition, we find that there are both common and segment‐specific levers for addressing digital inequalities between informal firms.
Keywords: African Research